From Practice to Principle and Back: Applying a New Realist Method to the European Union's Democratic Deficit. (May 2018) - Beetz, Jan Pieter
The prospect of a Brexit illustrates that the European Union's legitimacy deficit can have far-reaching political consequences. In normative political theory, realists take a keen interest in questions of legitimacy. Building on Bernard Williams' realist writings, I propose a two-step method of normative political theorization. Each step contains both a practice-sensitive phase and a practice-insensitive phase. First, the conceptualization of a norm should draw on conceptual resources available to agents within their historical circumstances. Second, the prescriptions that follow from this norm should take into account whether political order can be maintained. Applying this method to the European Union's democratic deficit yields, first, based on public opinion research, the norm of European deep diversity and, second, a set of prescriptions for a demoicratic confederacy. Thereby, I demonstrate that this realist method is able to yield political theories distinct from other philosophical approaches. Moreover, I contribute a realist theory to the normative literature in European Union studies.